(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To survey the use of antibiotics and factors associated with treatment outcomes in the Intensive Care Unit (ICU) of the Children’s Hospital 2. Subjects and Methods: A descriptive cross-sectional, retrospective study on 350 medical records of children hospitalized in ICU from June 2022 to June 2023. Results: The most used antibiotics were vancomycin (83.4%) and carbapenem (78%). Among 3,103 medical orders evaluated for antibiotic appropriatenes, 7.7% were inappropriate in terms of antibiotic selection, and 5.7% were inappropriate in terms of antibiotic dosage. The overall treatment success rate was 88.6%. Multivariate analysis revealed three factors associated with failure outcomes: septic shock (p = 0.002; OR 4.63; 95%CI 1.78 – 12.1), undergoing renal replacement therapy (p = 0.002; OR 6.53; 95%CI 1.99 – 21.49), and suspected invasive fungal infection (p = 0.002; OR 6.43; 95%CI 1.99 – 20.76) or confirmed invasive fungal infection (p = 0.001; OR 18.62; 95%CI 3.17 - 109.52). Conclusion: In general, antibiotic prescriptions and dosages were mostly adherent to current guidelines. Factors associated with failure treatment outcomes included septic shock, undergoing renal replacement therapy, and suspected or confirmed invasive fungal infections.